A Comparison of In-vitro PAH Bioaccessibility in Historically Contaminated Soils: Implications for Risk Management. Issue 8 (17th November 2021) - Esmaeili, Atefeh; Knox, Oliver; Juhasz, Albert; Wilson, Susan C.
ABSTRACT: This study compared polycyclic aromatic hydrocarbon (PAH) extractable fractions determined using six in-vitro methods, typically used for bioaccessibility/bioavailability predictions, for manufactured gas plant (MGP) historically contaminated soils, and evaluated the influence of soil properties. Methods used included depletive approaches for the bioaccessible fraction including butanol extraction (BuOH), non-buffered and buffered hydroxypropyl-β-cyclodextrin extractions (HPCD, Buf-HPCD), potassium persulfate oxidation (KPS) and solid-phase extraction using Tenax resin (Tenax); and a non-depletive polyoxymethylene solid phase extraction (POM) approach to determine the freely dissolved fraction. The KPS extraction removed the most ∑16 PAHs (1.5–77.1 fold more than other methods), while POM extracted the smallest ∑16 PAHs (average of 3.9–77.1 fold less than the other 5 methods). Soil properties were generally inconclusive as indicators of extractable fraction for the historically contaminated soils. Neither total nor organic carbon were important but soil particle size was most influential. Toxicity values and biodegradation endpoints derived using bioaccessibility-biodegradability linear regression models on the extracted PAH fractions ranged widely for the different soils, and illustrated the high variability for predicted ecotoxicity and bioremediation outcomes in risk managment application. The results demonstrated the importance of validation with intended soil end use and receptors for in-vitro assessment of bioaccessibility and bioavailability, to fully inform regulatory decision-making and risk management.